Perbandingan Tools Forensik Dalam Analisis Bukti Digital Pada Aplikasi Skype Menggunakan Framework NIST - Rizki Setyawan, Muhammad (Jurnal Mahajana Informasi, 2023)
In the rapidly evolving digital era, human communication has undergone significant changes thanks to instant messaging. Instant messaging enables us to easily and quickly connect with people around the world through mobile devices or computers. However, the use of instant messaging applications can have negative impacts such as fraud, harassment, illegal transactions, and more. Therefore, proper handling of cybercrime cases is crucial, which is why mobile forensics has become significant. Mobile forensics is a branch of digital forensics that aims to collect, analyze, and interpret data from mobile devices. This research aims to evaluate the performance of three forensic tools: Oxygen Forensic Suite, Belkasoft Evidence Center, and MOBILedit Forensic Express. It focuses on finding digital evidence related to activity information in the Skype application using the framework provided by NIST. The research results indicate that Oxygen Forensic Suite achieved the highest index value (98%), followed by Belkasoft Evidence Center (88%) and MOBILedit Forensic Express (84%).